(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
This study aims to review the existing issues associated with providing eco-friendly food to theworld’s population as a whole. If what we grew actually made it into people’s hands, we could easily feedmore people. It is more likely that rural communities will adopt, refine, and keep in place innovations interventions if they are informed by and based on indigenous agricultural methods. These greenpractices are seen as a viable option for use in organic farming since they are less harmful to theenvironment, more selective, biodegradable, cost-effective, renewable.